Stress testing supply chains and creating viable ecosystems - Dmitry Ivanov; Alexandre Dolgui (Operations Management Research, 2021)
Businesses and governments are becoming increasingly concerned about the resilience of supply chains and calling for their review and stress testing. In this conceptual essay, we theorize a human-centred ecosystem viability perspective that spans the dimensions of resilience and sustainability and can be used as guidance for the conceptualization of supply chain resilience analysis in the presence of long-term crises. Subsequently, we turn to the technological level and present the digital supply chain twin as a contemporary instrument for stress testing supply chain resilience. We provide some implementation guidelines and emphasize that although resilience assessment of individual supply chains is important and critical for firms, viability analysis of intertwined supply networks and ecosystems represents a novel and impactful research perspective. One of the major outcomes of this essay is the conceptualization of a human-centred ecosystem viability perspective on supply chain resilience.
Keywords: 510; Supply chain; Resilience; Viability; COVID-19 pandemic; Stress-test; Ecosystem; Intertwined supply network; Digital supply chain twin; Sustainability